2014
DOI: 10.1002/macp.201300649
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐Injection Method in High‐Temperature Two‐Dimensional Liquid Chromatography (2D HT‐LC)

Abstract: Comprehensively characterizing the relationship between the distributions with regard to chemical composition (CCD) and molar mass (MMD) of polyolefins is vital to establish structure–property relationships. Two‐dimensional high‐temperature liquid chromatography (2D HT‐LC), which couples a high‐temperature solvent gradient interactive chromatography (HT‐SGIC) step for compositional separation with a high‐temperature size exclusion chromatography (HT‐SEC) step for MMD determination in an on‐line manner is emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Then the Hypercarb column was loaded by flowing decanol at 0.5 mL/min through the column and using a loop of 300 μL. Multiple-injection method was used . 25 injections were made without eluting any polymer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the Hypercarb column was loaded by flowing decanol at 0.5 mL/min through the column and using a loop of 300 μL. Multiple-injection method was used . 25 injections were made without eluting any polymer.…”
Section: Methodsmentioning
confidence: 99%
“…Multipleinjection method was used. 24 25 injections were made without eluting any polymer. After the column was loaded, the following pump program (Table 1) was used to elute the polymer for fraction collection.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Larger injection volume was desired for better signal intensity. It had been demonstrated that large injection volume did not overload the column . This is likely because the polymer samples were injected in decane, the solvent with weak elution strength.…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] It has been shown that the adsorption strength of random ethylene/1-alkene copolymers is a function of concentration of the 1-alkene in the copolymers. The larger the concentration of the branches is, the smaller the adsorption of the copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Interactive HPLC systems, based on reversible adsorption and desorption of polyethylene on the surface of porous graphite at a temperature at which polyethylene stays in solution, were introduced into analytical laboratories starting from 2009 . It has been shown that the adsorption strength of random ethylene/1‐alkene copolymers is a function of concentration of the 1‐alkene in the copolymers.…”
Section: Introductionmentioning
confidence: 99%